Peran Hukum Islam dalam Membentuk Karakter Berempati Bagi Masyarakat Aceh - Amin, Maimun Abdurrahman; Rijal, Fakhrul (Al-Mizan, 2024)
The implementation of Islamic law in Aceh is not only aimed at maintaining social order but also at shaping empathetic character among the community. However, specific aspects related to the development of empathy have not received sufficient attention in previous research, which mostly focused on rule enforcement and sanctions. This study aims to explore the role of Islamic law in fostering an empathetic character in Aceh society. The method used is a descriptive qualitative approach involving in-depth interviews, participatory observations, and document analysis. The results show that the implementation of Islamic law in Aceh is effective not only in maintaining order but also in significantly shaping the empathetic character of the community. Social activities such as zakat and mutual assistance serve as effective means to foster care and solidarity among the people. This study concludes that Islamic law in Aceh has a strong social dimension and can create a more harmonious community that is empathetic and sensitive to the needs of others. The contribution of this study is to provide a deeper understanding of the social dimension of Islamic law, particularly in fostering empathetic character, which has not been widely addressed in previous studies.